ICSH guidelines for the laboratory diagnosis of nonimmune hereditary red cell membrane disorders. (18th March 2015) - King, M.‐J.; Garçon, L.; Hoyer, J. D.; Iolascon, A.; Picard, V.; Stewart, G.; Bianchi, P.; Lee, S.‐H.; Zanella, A.; the International Council for Standardization in Haematology
Summary Introduction Hereditary spherocytosis (HS), hereditary elliptocytosis (HE), and hereditary stomatocytosis (HSt) are inherited red cell disorders caused by defects in various membrane proteins. The heterogeneous clinical presentation, biochemical and genetic abnormalities in HS and HE have been well documented. The need to raise the awareness of HSt, albeit its much lower prevalence than HS, is due to the undesirable outcome of splenectomy in these patients. Methods The scope of this guideline is to identify the characteristic clinical features, the red cell parameters (including red cell morphology) for these red cell disorders associated, respectively, with defective cytoskeleton (HS and HE) and abnormal cation permeability in the lipid bilayer (HSt) of the red cell. The current screening tests for HS are described, and their limitations are highlighted. Results An appropriate diagnosis can often be made when the screening test result(s) is reviewed together with the patient's clinical/family history, blood count results, reticulocyte count, red cell morphology, and chemistry results. SDS–polyacrylamide gel electrophoresis of erythrocyte membrane proteins, monovalent cation flux measurement, and molecular analysis of membrane protein genes are specialist tests for further investigation. Conclusion Specialist tests provide additional evidence in supporting the diagnosis and that will facilitate the management of the patient. In the case of a patient's clinical phenotype being more severe than the affected members within the immediate family, molecular testing of all family members is useful for confirming the diagnosis and allows an insight into the molecular basis of the abnormality such as a recessive mode of inheritance or a de novo mutation.